Estudo experimental e numérico da convecção tropical sobre a Amazônia em diferentes regimes de particulado antropogênicos e possíveis modificações climáticas - Silvério, Antônio Charles (2006)
The microphysics processes, represent nowadays, one of the most crucial uncertainties in the understanding of the tropical convection. This is due to the fact that great part of the energy necessary for the tropical atmospheric movements is released by the microphysics processes. Then a correct representation of the microphysics processes in general circulation models involving clouds and his interaction with the atmospheric circulation in larger scales is an essential condition for the obtention of good results in climatic forecast and simulations of global climatic changes. This work consist of a study (revision) of the theory atmospheric aerosols and a characterization of the Amazonian area, a complete description of the field experiments EMfiN!/LBA/SMOCC, as well, a study of the relationship between the condensation nuclei and the cloud microstructure, up to interaction of the clouds with the thermodynamic structure of the atmosphere of larger scale, possible climatic modifications provoked by anthropogenic factors (forest fire) and also studies using numerical models: one of parcels, one bin-microphysics cloud model and another of ensemble of clouds, all were initiated with data from the above mentioned experiments. The experimental and numerical results suggest that the pollution inhibits the formation and the development of the precipitation in the liquid phase (warm rain), and it alters the radiation flow, with significant consequences in the climatic, at least in regional scale.